Software-defined cross-domain scheduling mechanism for time-sensitive networking - Shuo WANG; Yudong HUANG; Tao HUANG; Ru HUO; Yunjie LIU (Tongxin xuebao)
For the cross domain scheduling problem of time-sensitive network, a software-defined cross-domain scheduling mechanism for time-sensitive networking was proposed, which was based on three kinds of wide area clock synchronization technology to ensure nanosecond inter-domain time synchronization.Then, a time slot conflict-free cross domain scheduling model was proposed to solve the problem of time slot alignment caused by inter-domain link delay.The time slot conflict-free constraints were used to strictly limit the arrival time of cross-domain traffic at the edge node.Finally, the gate control list of fusion domains for global scheduling was calculated online.The simulation results show that the model can schedule hundreds of time-sensitive traffic in a typical cross-domain remote control scenario, and has a feasible algorithm execution time in seconds.